The Instrumental Character of the Concept of Sustainability Focusing to the Institutionalist Theory - Piffer, Vanessa; PEDRO FILHO, Flávio de São; Luz Neto, Leonardo Severo da; Albuquerque, Luiz Carlos Cavalcanti de (International Journal for Innovation Education and Research, 2019)
In organizations, we seek to adapt to the good practices of a relationship with nature, transforming technologies, processes and structural and productive redesign. Reflections such as these motivate research supported by the Institutionalist Theory and the assumptions of sustainability. The general objective here is to carry out a theoretical-conceptual study on the instrumental character of the concept of sustainability in focusing to the of institutionalist theory; and to the results, the specific objectives of contextualizing the concept of sustainability (1), addressing the main concepts raised in the face of institutionalist theory (2), and analyzing the approach of the conceptual perspectives considered in this research (3). The question to be answered in this study is: what is the instrumental character of the concept of sustainability in the face of institutionalist theory? The Content Analysis Method and data analysis techniques are applied in qualitative research, such as cleavage and categorization. As a result, it brings a virtuous circle of conceptual relation in evidence; points out inequality of behavior in organizations, making it difficult to achieve sustainability; Criticism points to the lack of employee awareness of the rules. We also look at organizational levels that reflect on sustainability. Conceptual applicability converts the commitment to protect and conserve natural resources, while at the same time channeling real benefits to all who are around the institution that promotes the activities. These concepts will result in a balance between the constraints that lead to scarcity and progress on the sustainability tripod; are isomorphic measures that are somehow beneficial in the relationship between the environment and the social and economic.